2018
DOI: 10.1136/bmjpo-2018-000334
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry monitoring in asthmatic children in Lombardy Region, Italy

Abstract: ObjectivesTo evaluate the diagnostic and therapeutic approaches in a cohort of asthmatic children before and after starting drug therapy.MethodsData were retrieved from administrative databases of the Lombardy Region. The study population was composed of 78 184 children born in the Lombardy Region in 2002 and followed until their 10th birthday.Children with at least one antiasthmatic drug prescription per year (with the exclusion of nebulised suspension/solution formulations) in 2 consecutive years and at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…One of the main reasons spirometry is under-used is that children may find the manoeuvre difficult to perform, and the success rates in the younger age groups may be low 9 10. A study reported that only 32.4% of children aged 5–8 years with potential asthma had at least one spirometry undertaken either in the year before (6.4%) or the 2 years after (29.7%) the first asthma treatment 11. Moreover, only one-third of children with asthma were referred for spirometry,12 and only half of children hospitalised with asthma underwent spirometry during follow-up 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main reasons spirometry is under-used is that children may find the manoeuvre difficult to perform, and the success rates in the younger age groups may be low 9 10. A study reported that only 32.4% of children aged 5–8 years with potential asthma had at least one spirometry undertaken either in the year before (6.4%) or the 2 years after (29.7%) the first asthma treatment 11. Moreover, only one-third of children with asthma were referred for spirometry,12 and only half of children hospitalised with asthma underwent spirometry during follow-up 13.…”
Section: Introductionmentioning
confidence: 99%
“… 9 10 A study reported that only 32.4% of children aged 5–8 years with potential asthma had at least one spirometry undertaken either in the year before (6.4%) or the 2 years after (29.7%) the first asthma treatment. 11 Moreover, only one-third of children with asthma were referred for spirometry, 12 and only half of children hospitalised with asthma underwent spirometry during follow-up. 13 Others found that only 10–21% of general practitioners and paediatricians used spirometry consistently in childhood asthma management.…”
Section: Introductionmentioning
confidence: 99%